2019
DOI: 10.1371/journal.pone.0218626
|View full text |Cite
|
Sign up to set email alerts
|

Short-term traffic speed prediction under different data collection time intervals using a SARIMA-SDGM hybrid prediction model

Abstract: Short-term traffic speed prediction is a key component of proactive traffic control in the intelligent transportation systems. The objective of this study is to investigate the short-term traffic speed prediction under different data collection time intervals. Traffic speed data was collected from an urban freeway in Edmonton, Canada. A seasonal autoregressive integrated moving average plus seasonal discrete grey model structure (SARIMA-SDGM) was proposed to perform the traffic speed prediction. The model perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…In past research, traffic flow data was mostly processed as time series data with intervals of 10-minutes, 5-minutes, or 2minutes. For the time series prediction problem, the shorter the time interval, the more practical application value it has and the nonlinearity of the data has [40], [41]. Meanwhile, for traffic flow data, short intervals will increase the sparsity of the data.…”
Section: Input Matrix Lstm Layermentioning
confidence: 99%
“…In past research, traffic flow data was mostly processed as time series data with intervals of 10-minutes, 5-minutes, or 2minutes. For the time series prediction problem, the shorter the time interval, the more practical application value it has and the nonlinearity of the data has [40], [41]. Meanwhile, for traffic flow data, short intervals will increase the sparsity of the data.…”
Section: Input Matrix Lstm Layermentioning
confidence: 99%
“…In short-term traffic forecasting, estimating traffic conditions usually focuses on speed and flow predictions. Speed prediction, in particular, is directly related to proactive traffic control system development [6,7]. However, estimating vehicle speed is problematic because it is affected by driver behaviour, road environment and the spatial and temporal complexities of traffic conditions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although all these time series methods are widely used in traffic prediction, the majority of the research found in the literature focuses on applying these methods on large time windows [46]. A study by Song et al on short-term traffic speed prediction provides a comparison between four prediction methods with different data collected in a varying time window ranging from 1 min up to 30 mins [47]. The study proposes a seasonal discrete grey model (SDGM) and compares the prediction accuracy with the seasonal autoregressive integrated moving average (SARIMA) model, artificial neural network (ANN) model, and support vector regression (SVR) model.…”
Section: Autoregressive (Ar) Modelmentioning
confidence: 99%